THE INFLUENCE OF EMPLOYEE VALUES ON PROJECT SUCCESS RATE IN THE KENYAN PUBLIC SECTOR ORGANIZATIONS: LESSONS FROM KENYA CIVIL AVIATION AUTHORITY - Ongaga, Charles Kombo; Nkirina, Dr. Severina (International Journal of Entrepreneurship and Project Management, 2017)
Purpose: The purpose of the study was to investigate the influence of employee values on project success rate in the Kenyan Public sector organizations, from the perspective of Kenya Civil Aviation Authority. Four aspects of employee values were assessed as follows; employee integrity, employee commitment to the organization, fairness in treating employees, teamwork, and employee responsiveness. Methodology: The research has adopted a Descriptive research design which was used to plan the study and a target population of 442 staff members of 8 departments of Kenya Civil Aviation Authority (KCAA) who are directly involved with implementation of projects was used. A sample of 156 respondents was selected and questionnaires were used to collect primary data from them. The data was analyzed using descriptive and inferential statistics and presented in tables and bar charts. Statistical Package for Social Sciences (SPSS) version 23 assisted in generating results. The tool was found to be very reliable with Cronbach's Alpha coefficient of 0.965. Findings: The study revealed that employee values as an element of organizational culture had a significant influence on the success rate of public sector projects (Karl Pearson correlation coefficients of 0.901). Policy recommendation: The finding further showed that implementation of projects in KCAA was largely successful. The study recommends the need to develop and adopt a culture that promotes employee values such as integrity, team work and commitment to the vision and goals of the organization in order to enhance success rate in implementation of projects in public sector entities. Further research can be conducted to show the influence of employee remuneration on project success rate in public sector organizations.